CYTO-DEPRESSIVE POTENTIAL OF GANODERMA LUCIDUM, PLEUROTUS OSTREATUS AND THEIR BINARY COMBINATIONS AGAINST MERISTEMATIC CELLS OF ALLIUM CEPA L. - UDDIN PK, MOYEN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The current study is designed to evaluate the cyto-depressive effects of Ganoderma lucidum (GL) and Pleurotus ostreatus (PO) and their binary amalgams (GL+PO) on meristematic cells of Allium cepa L. Methods: Experiments were assessed by utilizing A. cepa bioassay. Results: Onion knobs were exposed to 500 μg/mL, 1000 μg/mL, and 2000 μg/mL groupings of the concentrates for naturally visible and minute examination. The concentrates essentially repressed the root development of A. cepa L. contrasted with the control in a period of treatment and concentration-dependent manner (p<0.05). In addition, photomicrographs revealed chromosomal aberrations extending from c-mitosis, stickiness, and bridges in the root tip meristematic cells of A. cepa. All mushroom extracts demonstrated remarkable cyto-depressive impacts on meristematic cells of A. cepa L. with some changeability. Conclusion: In view of the results come out, GL and PO could be considered as potential sources of anticancer mixes. Notwithstanding, additionally thinks about are essential for disengagement and portrayal of the bioactive mixes and more examination on their pharmacological properties is required. It is first report in Bangladesh where we studied cyto-depressive role of edible mushrooms, Ganoderma lucidum (GL) and Pleurotus ostreatus (PO).